Multifield Problems in Solid and Fluid Mechanics - Helmig, Rainer; Mielke, Alexander; Wohlmuth, Barbara I. (Lecture Notes in Applied and Computational Mechanics,, 2006)
Understanding the interaction between various processes is a pre-requisite for solving problems in natural and engineering sciences. Many phenomena can not be described by concentrating on them in isolation - therefore multifield models and concepts that include various kinds of field problems and processes are needed. This book summarizes the main scientific results of the Collaborative Research Center on Multifield Problems in Continuum Mechanics (Sonderforschungsbereich Mehrfeldprobleme in der Kontinuumsmechanik, SFB 404) funded by the German Research Foundation (DFG) from 1995-2006. The book is divided into three main sections: A: Volume-Coupled Problems, devoted to fields which are coupled inside the processing domain or volume, B: Boundary-Coupled Problems, here physical fields and processes are coupled via domain boundaries, C: Fundamental Methods, search into the mathematical concepts and backgrounds of multifield and multiscale modeling.